AN INVESTIGATION OF THE PROBLEMS FACED BY VEGETABLE GROWERS REGARDING POST-HARVEST PRACTICES IN DISTRICT FAISALABAD - Khan, HS; Chaudhry, KM; Ashraf, I; Usman, M; Ejaz, R; Khadim, MM (Biological and Clinical Sciences Research Journal, 2020)
Vegetables have important role in daily food which have essential nutritionals because they have a significant source of vitamins, sugar and dietary fibre as well as antioxidants. The study was conducted in district Faisalabad. Tehsil Sammundri and Jaranwala were selected purposively, because there are maximum vegetables growers. The population of Jaranwala and Sammundri were 178 and 241 vegetable growers respectively making a total population of 419 according to the list of agricultural extension department. Sample size was 202 by using online software (survey system.com) keeping confidence interval 5% and confidence level 95%. Proportionate sampling was used to select the respondents in these two tehsils. By using proportionate sampling respondents of tehsils named Jaranwala and Sammundri were 86 and 116 respectively. Results show that majority of respondents were falling between 41-60 years age interval, cultivating the vegetables. About one third 31.7% of the respondents were matriculation those farmers having knowledge about education importance and values. Manual washing is method of washing the vegetables by using of clean water this method was ranked 4th, it secured mean value of 3.82. In studied areas mostly farmers were using simple packing including polythene, plastic bags it ranked 6th. About vast majority of 90.1% respondents have been used the simple packing for vegetables it secured mean value of 3.26. In transportation process of vegetables over whelming majority 99% of respondents were using less expensive and easily approach able vehicle that was loader Rikshaw, which ranked 1st as compared to other vehicle which secured a mean value of 4.25. About vast majority 84.2% respondents were facing the problem of middle man involvement in markets. Middle man has most important role between customer and farmers that was observed, it ranked 17th and it secure mean value of 3.25. There was maximum issue of technology was noticed that they had no awareness regarding the machinery. They had faced the issue of markets and middle man commission. Government should pay attention toward infrastructure, markets governance and reduce the commission of middle man by involving the responsible authorities. Government institutes should deliver the proper guideline related to vegetables post-harvest problems to improve the quality and quantity of products.